PROPOSED MARKETING STRATEGY FOR WORK FROM HOME APPLICATION BY TELKOM INDONESIA - Kautsar, Kemal
In 2019, the world faced a drastic change in terms of communication and physical activities among people. An acute respiratory syndrome called COVID-19, an airborne virus spread via droplets made when people are coughing or sneezing, spreads the world like never before. People who caught the virus have a risk of catching pneumonia and death is a possibility because of the complications caused by the virus. Although it’s a flu-like virus, there are no antivirus or medicine available to combat the COVID-19 virus. Therefore, unlike common flu, the massive spread of the virus among people is inevitable until the anti-virus is formulated. To limit the spread of the virus until the anti-virus is formulated, WHO recommends people around the world to limit their physical contact with each other. Governments around the world try to limit the spread of the virus by limiting their citizens’ physical contact by law. However, this complicates things for the economy. Physical contact limitation meaning people can’t just work in the office as usual since it can risk the spread of the virus. To avoid bankruptcy because of no business activity, a compromise was made by the companies to switch their business to remote working type. Connected using the internet, workers can still communicate with each other using a work from home (WFH) application. A WFH application is an application that enables workers to connect each other via text, video conferencing, or sharing screen to show presentation slides. PT. Telkom Indonesia is a state-owned enterprise owned by the Indonesian government that is engaged in telecommunication, a backbone of internet technology. Although the company also offers internet service to the customers, Telkom Indonesia doesn’t have a WFH application in their product lineup. The author of this study felt it is a missed opportunity for Telkom Indonesia not to have a WFH application in their product offerings. This study’s goal is to understand what is the best marketing strategy to market the future WFH application for the company. A strategic management process is used in this study to craft the best marketing strategy for the WFH application. The process starts from external and internal environment scanning and culminates into SWOT analysis. Segmenting, targeting, and positioning (STP) method used to choose which target market to tap into then a further analysis using TOWS matrix to choose suitable strategies given the opportunities or threat presented from the external factor; strength and weakness owned by the company. The proposed marketing strategy then formulated from the combination of the result of STP analysis and the TOWS analysis results in what is the best target segment to tap into and what is the suitable marketing strategy for the target segment. The ensuing implementation program then formulated using the proposed marketing strategy.